Assessing the effectiveness of World Bank investments: The gender dimension - Claire Lauterbach; Elaine Zuckerman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Today it is widely acknowledged that increasing the gender sensitivity of development aid increases its effectiveness. This report evaluates the extent to which the World Bank integrates gender concerns into its policies and investments, pointing out structural, financial and policy gaps that risk negatively impacting women in countries with Bank investments. The report evaluates Bank investments in 'agriculture and rural development'; 'sexual and reproductive health and HIV/AIDS'; and 'conflict prevention and post-conflict reconstruction', finding that the Bank superficially includes women's concerns in its investments. The report concludes with recommendations for making World Bank investments responsive to women's needs and rights.
Keywords: O200; 330; World Bank; development aid; gender; effectiveness; Entwicklungshilfe; Gleichberechtigung; Wirkungsanalyse